Pharmacodynamic Functions of Synthetic Derivatives for Treatment of Methicillin-Resistant Staphylococcus aureus (MRSA) and Mycobacterium tuberculosis - Dinarvand, Mojdeh; Spain, Malcolm P.; Vafaee, Fatemeh (Frontiers in Microbiology, 2020)
Drug resistant bacteria have emerged, so robust methods are needed to evaluate combined activities of known antibiotics as well as new synthetic compounds as novel antimicrobial agents to treatment efficacy in severe bacterial infections. Marine natural products (MNPs) have become new strong leads in the drug discovery endeavour and an effective alternative to control infections. Herein, we report the bioassay guided fractionation of marine extracts from the sponges Lendenfeldia, Ircinia, and Dysidea that led us to identify novel compounds with antimicrobial properties. Chemical synthesis of predicted compounds and their analogues has confirmed that the pro-posed structures may encode novel chemical structures with promising antimicrobial activity against the medically important pathogens. Several of the synthetic analogues exhibited po-tent and broad spectrum in-vitro antibacterial activity, especially against the Methicillin-resistant Staphylococcus aureus (MRSA) (MICs to 12.5 µM), Mycobacterium tuberculosis (MICs to 0.02 µM), uropathogenic Escherichia coli (MIC 6.2 µM), and Pseudomonas aeru-ginosa (MIC 3.1 µM). Checkerboard Assay (CA) and Time-Kill Studies (TKS) experiments analyzed with the a pharmacodynamic model, have potentials for in vitro evaluation of new and existing antimi-crobials. In this study, CA and TKS were used to identify the potential benefits of an antibiotic com-bination (i.e., synthetic compounds, vancomycin and rifampicin) for the treatment of MRSA and M. tuberculosis infections. CA experiments indicated that the association of compounds 1a and 2a with vancomycin and compound 3 with rifampicin combination have a synergistic effect against a MRSA and M. tuberculosis infections, respectively. Furthermore, the analysis of TKS uncovered bactericidal and time-dependent properties of the synthetic compounds that may be due to variations in hydrophobicity and mechanisms of action of the molecules tested. The results of cross-referencing antimicrobial activity, and toxicity, CA, and Time-Kill exper-iments establish that these synthetic compounds are promising potential leads molecule, with a favourable therapeutic index for antimicrobial drug development.